Photovoltaic shunt active power filter based on indirect self-charging with step size error cancellation and simplified adaptive linear neuron - Mohd Zainuri, Muhammad Ammirrul Atiqi (2017)
Current harmonics is one of the main power quality problems which can be mitigated by using shunt active power filter (SAPF). Integrating SAPF with photovoltaic (PV), also known as PV SAPF, is among the best option as it provides alternative energy source to operate the SAPF rather than depending on energy from the grid supply and at the same time maintaining Total Harmonics Distortion (THD) below 5%. DC-link capacitor voltage control and harmonics extraction algorithms, are giving high impact to overall SAPF’s performance. In DC-link capacitor voltage control, the existing works on direct self-charging algorithm still have many drawbacks in terms of overshoot, undershoot and response time, especially during dynamic operation.